Microstructural influence on anodic film formation and corrosion resistance in anodized high-strength aluminium alloys - Araujo, João Victor de Sousa (2025)
This study investigates how microstructure influences anodic film formation and corrosion resistance in high-strength aluminum alloys anodized in tartaric-sulfuric acid (TSA) at 14 V. The alloys studied include AA2024-T3 (Al-Cu-Mg), AA2198-T8/T851 (Al-Cu-Li), and AA7475-T761 (Al-Zn-Mg). Microstructural analyses were performed using scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) and scanning Kelvin probe force microscopy (SKPFM) to evaluate the morphology, size, density, and chemical composition of constituent intermetallic particles (IMPs) in these alloys. The AA2024-T3 alloy contains three main types of IMPsAl-Cu-Mg, Al-Cu-Fe-Mn, and Al-Cu-Fe-Mn-Si all with copper content exceeding 15 wt.%, classifying them as high-copper-containing particles. Similarly, the AA2198-T8/T851 alloys predominantly feature high-copper-content Al-Cu-Fe particles (> 15 wt.%). In contrast, the AA7475-T761 alloy has the lowest particle density, with IMPs exhibiting either high-coppercontent (> 27.5 wt.%) or low-copper-content (< 7 wt.%). The behaviour of these IMPs during anodizing was investigated using transmission electron microscopy (TEM), SEM-EDX, atomic force microscopy (AFM), and cross-sectional analysis of anodic films through ultramicrotomy and mechanical bending techniques. An inverse relationship was observed between the thickness of the anodic film and the current density measured during anodizing, with alloys containing higher densities of constituent IMPs exhibiting higher current densities but thinner anodic films. High-copper-containing particles dissolved rapidly during the initial stages of anodizing, forming micrometric cavities on the surface and within the anodic film. Conversely, Si-containing and low-copper-containing IMPs in the AA2024-T3 and AA7475-T761 alloys, respectively, showed a slower dissolution rate compared to the aluminum matrix, embedding them within the anodic film and creating highly porous regions above these particles. Corrosion resistance was further evaluated through immersion tests in chloride-containing solutions to assess the impact of defects induced by the dissolution of constituent IMPs. Optical microscopy, SEM-EDX, and ultramicrotomy enabled crosssectional analysis of corrosion sites, confirming that defects at the film/alloy interface, caused by dissolved high-copper-content IMPs, initiate localized corrosion by allowing electrolyte penetration that compromises the protective properties of the anodic film. In contrast, low-copper-content IMPs in the AA7475-T761 alloy resulted in fewer critical defects, thus contributing to relatively higher corrosion resistance. The study also highlights the importance of using appropriate techniques to analyse pitting corrosion in anodized aluminum alloys. Characterization techniques such as optical microscopy, SEM, profilometry, and cross-sectional analysis revealed significant variations in pit morphology and depth, indicating that surface-only observations may lead to misinterpretations. Accurate characterization through a combination of these methods is essential for a comprehensive understanding of pitting corrosion morphology and extent. These findings underscore the influence of constituent IMPs on the characteristics of anodic film formation and the defects they induce, directly impacting the corrosion resistance of anodized aluminum alloys. This insight is critical for advancing microstructural control and improving the anodizing process to optimize the performance of these materials.